PENGARUH PEMAHAMAN PERATURAN PERPAJAKAN DAN PENERAPAN E-FILLING TERHADAP KEPATUHAN WAJIB PAJAK - Nida Putri Rahmayanti; Imawati Yousida; Susmita Dian Indiraswari (Sekolah Tinggi Ilmu Ekonomi Nasional (STIENAS) Banjarmasin, 2025)
This study aims to examine the effect of understanding tax regulations and the implementation of E-Filling on taxpayer compliance. This study uses a quantitative method with primary data, statistical tools using SPSS version 26. The sample in the study amounted to 149 respondents. The results of the study indicate that understanding tax regulations has a partial effect on taxpayer compliance and the implementation of the E-Filling system has a partial effect on taxpayer compliance. This means that taxpayer compliance is greatly influenced by understanding tax regulations. Because with taxpayers understanding tax regulations, taxpayers will understand their rights and obligations as taxpayers. And with the existence of a technology system using E-Filling, it will make it easier for taxpayers to carry out their tax obligations